Retrospective Analysis of Non-Contact ACL Injury Risk: A Case Series Review of Elite Female Athletes - Herrington, Lee; Cooke, Ros (Journal of Sports Medicine and Therapy, 2017)
Background: Literature on ACL injury is limited when assessing for the presence and interaction of multiple risk factors simultaneously. Identifying risk factor interaction may increase the impact of prevention programmes to target ACL injury reduction. The aim of this study was to retrospectively assess ACL injured female athletes to identify which modifiable and non-modifiable risk factors were present at the time of injury. Method: Seventeen female athletes who had sustained a non-contact ACL injury were interviewed retrospectively to assess for the presence of reported risk factors for ACL injury. Result: This retrospective analysis ACL injury cases highlighted a number of factors which were present with high frequency across this group of cases. All had non-contact ACL injury occurring during cutting or landing, which suggests a predisposing deficit in neuromuscular control. This poor neuromuscular control could be exacerbated by the presence of fatigue identified within the cohort. This poor control could be further influenced by the fact a majority of athletes had another significant injury in the 12 weeks prior to ACL injury. The restriction to training could have either decreased fatigue resistance, or potentially changed their movement pattern because of the method of injury management undertaken. Conclusion: This case series provides insight into the interaction of risk factors for ACL injury in sportswomen, with the presence of another injury disrupting training, decreasing the athletes work capacity and fatigue resistance, being compounded perceived or actually elevated levels of fatigue, leading to the potential for abhorrent movement patterns and increased injury risk.